Osnove urejanja površinskih vodotokov - Kramer Stajnko, Janja (2020)
Fundamentals of Surface Water Regulation. The book deals with the problem of surface water regulation, which has receieved a lot attention recently due to increasingly extreme and unpredictable weather phenomena. Improperly regulated sections of riverbeds, reckless human interventions into watercourses, and especially changing the natural drainage regime of watercourses, can cause a lot of damage in wider areas in case of occurence of high waters. Regulation actions on watercourses have to be planned comprehensively, where all key elements e.g. phisical, biological and human have to be taken into account. The book considers the theoretical background of hydraulics of open channel flow, fundamentals of river morphology, basic methods of data collection for planning the river regulation measures, the problems of sediment transport in watercourses and comprehensive review of possible regulation actions, including materials and performance.
Keywords: Open channel flow; surface watercourses; river morphology; sediment transport; regulation measures; sustainable measures